2011
DOI: 10.1007/s10653-011-9419-x
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic mobility in the amended mine tailings and its impact on soil enzyme activity

Abstract: The objectives of this study were to elucidate the effects of soil amendments [Ferrous sulfate (Fe(II)), red mud, Fe(II) with calcium carbonate (Fe(II)/L) or red mud (RM/F), zero-valent iron (ZVI), furnace slag, spent mushroom waste and by-product fertilizer] on arsenic (As) stabilization and to establish relationships between soil properties, As fractions and soil enzyme activities in amended As-rich gold mine tailings (Kangwon and Keumkey). Following the application of amendments, a sequential extraction tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 31 publications
0
21
0
2
Order By: Relevance
“…The rise in metal extractability (Mn, Cu and Zn) did not act in detriment of β-glucosidase activity, as those soil characteristics fitted well together, with high negative factor loadings on PC1. This result is in years since iron-grit was applied, and Koo et al (2012) reported that β-glucosidase activity increased over the control with the addition of FeSO4 and iron grit separately.…”
Section: Resultsmentioning
confidence: 84%
“…The rise in metal extractability (Mn, Cu and Zn) did not act in detriment of β-glucosidase activity, as those soil characteristics fitted well together, with high negative factor loadings on PC1. This result is in years since iron-grit was applied, and Koo et al (2012) reported that β-glucosidase activity increased over the control with the addition of FeSO4 and iron grit separately.…”
Section: Resultsmentioning
confidence: 84%
“…공시재료 특성 분석결과 본 연구에서 현장시험이 수행된 대조구 토양 및 인공토양 제조에 사용한 바닥재의 화 학적 특성은 토양질 분석결과 현장 시험구를 설치한 후 3회 (2016년 6, 7, 10월)에 걸쳐 실험구 및 대조구 토양의 특성을 분 석하였다 (Table 3) Ahmad et al, 2012;Koo et al, 2012;Lee et al, 2011). 토양 내 중금속 함량의 경우 대조구 및 실 험구에서 채취한 시료 모두 국내 토양환경보전법의 기준치를 만족하는 것으로 나타났으나, 실험구의 함량이 대조구 …”
Section: Resultsunclassified
“…Samples were then placed in a refrigerator at 4°C (Gianfreda et al 2005;Lai et al 1999;Li et al 2015;Perez-de-Mora et al 2005;Jin et al 2014;Qu et al 2011;Romero et al 2005;Moreno et al 2009;Koo et al 2012) to preserve biological properties (Claassens et al 2008;Maboeta et al 2006), and chemical analysis was carried out within 3 weeks. Immediately prior to analysis, samples were removed from the refrigerator, placed on petri dishes and laid on the table for air-drying.…”
Section: Methodsmentioning
confidence: 99%